Distribution, mapping, sustainable harvesting and marketing of laurel leaves (Cinnamomum mindanaese Elmer) in Boljoon, Cebu, Philippines - Alburo, Hemres M.; Alburo, Rosalyn P.; Gabucan, Mario F.; Albiso, Cesilo (Annals of Tropical Research, 2018)
Cinnamons are popularly known as spice and flavoring to many foods. In the Philippines, laurel leaves (Cinnamomum mindanaense) are commonly used as spice to many Filipino dishes. In Cebu, C. minadanaense abundantly grows in San Antonio, Boljoon, where the community harvests and trades leaves for decades. An inventory of C. mindanaense was made to establish baseline data on the number of trees per diameter classes. A survey on knowledge, harvesting and marketing of C. mindanaense was also conducted. Trees by diameter class were mapped using ArcMap 10.5. A total of 5332 trees were inventoried and grouped into five diameter classes namely 10cm and below, 11-20cm, 21-30cm, 31-40cm and above 40cm. Results show that trees are generally small and growing on limestone areas both within Alienable and Disposable lands and timberland areas. Ninety-two percent or 4918 trees have diameter of 20cm or less. Leaves are harvested mostly by cutting all branches especially during dry season. Harvesting is generally made once a year. Over mature leaves tend to reduce quality due to disease and insect damage. Cut branches are sundried for 3 days then leaves are removed and traded to middlemen in the village at P10-15 per kilo or in Cebu City at P20-25/kg. Average harvest of farmers is 8 sacks per year with 20-25kg/sack. Income derived from cinnamons is only secondary. Development of products from the branches left or from the dried laurel leaves may be explored to enhance community livelihood and increase economic potential of the species.